Galectin-3-Mediated Glial Crosstalk Drives Oligodendrocyte Differentiation and (Re)myelination - Thomas, Laura; Pasquini, Laura Andrea (Frontiers in Cellular Neuroscience, 2018)
Galectin-3 (Gal-3) is the only chimeric protein in the galectin family. Gal-3 structure comprises unusual tandem repeats of proline and glycine-rich short stretches bound to a carbohydrate-recognition domain (CRD). The present review summarizes Gal-3 functions in the extracellular and intracellular space, its regulation and its internalization and secretion, with a focus on the current knowledge of Gal-3 role in central nervous system (CNS) health and disease, particularly oligodendrocyte (OLG) differentiation, myelination and remyelination in experimental models of multiple sclerosis (MS). During myelination, microglia-expressed Gal-3 promotes OLG differentiation by binding glycoconjugates present only on the cell surface of OLG precursor cells (OPC). During remyelination, microglia-expressed Gal-3 favors an M2 microglial phenotype, hence fostering myelin debris phagocytosis through TREM-2b phagocytic receptor and OLG differentiation. Gal-3 is necessary for myelin integrity and function, as evidenced by myelin ultrastructural and behavioral studies from LGALS3−/− mice. Mechanistically, Gal-3 enhances actin assembly and reduces Erk 1/2 activation, leading to early OLG branching. Gal-3 later induces Akt activation and increases MBP expression, promoting gelsolin release and actin disassembly and thus regulating OLG final differentiation. Altogether, findings indicate that Gal-3 mediates the glial crosstalk driving OLG differentiation and (re)myelination and may be regarded as a target in the design of future therapies for a variety of demyelinating diseases.